An analysis about the relationship between the cloud computing model and ITIL v3 2011 - Pinto, António João da Silva Cortez (2021)
Cloud Computing is widely recognized as a recent computing paradigm of digital transformation in which scalable and elastic computational resources are delivered as a service through Internet technologies. Its characteristics made this business model increasingly adopted by organizations reaching business goals. Besides its benefits, some risks may impact organizations internally and, in the way they deliver their services to their clients. Therefore, it became important to understand the impacts of the Cloud model on the way companies organize their processes. The goal of this work is to investigate which are the main impacts arising from the Cloud Computing model currently impacting Information Technology Infrastructure Library framework processes. The methodology selected will be through semi-structured interviews with knowledgeable professionals to effectively collect practical information that, according to the Systematic Literature Review performed, could not be collected by the traditional literature. By analyzing the Systematic Literature Review results, several processes of this framework were affected, which may lead to a need for reframing it. Although the organization’s approach to this model must be enhanced and adapted to a new reality, the empirical insights collected from semi-structured interviews, suggest that the framework does not need to be reframed, and ITIL v3 2011 most impacted processes by the introduction of the Cloud-based model, are Change Management and Incident Management.